FACTORS AFFECTING WILLINGNESS TO PAY TAXES ON INDIVIDUAL TAXPAYERS AT PRATAMA SURABAYA TEGALSARI TAX OFFICE - Hariyadi Setyonugroho; Bayu Sardjono (STIE Perbanas Surabaya, 2013)
Tax is one of the countrys largest revenues and it also constitutes a form of self-reliance infinancing the construction of a nation. The willingness of taxpayers in tax payments is importantin tax collection. Therefore, when there is a lack of willingness to pay taxes, it will result inthe indirect taxes which can be felt by the taxpayers. It is because the public have never knownthe existing concrete reward of money spent for paying the tax. This research uses several hypothesesto determine the effects of the variables in this study. The samples are individual taxpayerswho are listed on Pratama Surabaya Tegalsari Tax Office and have a Taxpayer IdentificationNumber as well as making payment on the Pratama Surabaya Tegalsari Tax Office.Linear regression analysis is used to test the research hypotheses. The result shows that theawareness of paying taxes has no effect on the willingness to pay taxes, while the knowledgeand understanding of tax rules, a good perception of the effectiveness of the taxation system,and service quality affects the willingness to pay taxes.